Good recovery of prostate carcinoma with spine metastases to T9 following laminectomy - Ahmad, Muhammad Wafiuddin; Roslan, Ahmad Faizal; Jasni, Muhammad Jasfizal; Mor Japar Khan, Ed Simor Khan (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
We present a rare case of a patient diagnosed with prostate carcinoma with spine metastases of T9 vertebrae whom had good neurological recovery following decompression. Six months post surgery patient was able to ambulate with a walking aid. About 6.7% of prostate cancer patient will have spinal compression. A 65 year old gentleman diagnosed with prostate carcinoma 2 years ago done orchidectomy and chemotherapy, presented with progressive worsening of bilateral lower limb weakness and numbness for 5 months duration associated with back pain. On admission the Visual Analog Score for back pain was 5/10. Neurological examination revealed complete paralysis of bilateral lower limb, absent bilateral knee and ankle jerk and sensation. Plain radiograph and MRI showed osteoblastic bone metastases at T9 level with epidural extension. A wide laminectomy of T9 vertebra while preserving the bilateral facet joint was done. No instrumentation was needed as there were no significant vertebral body collapsed due to the osteoblastic nature of the lesion. Six months after the surgery patient showed good neurological recovery with the power of MRC grade 4 for bilateral lower limb and Visual Analog Score for back pain reduced significantly. Numerous study had shown poor outcome in Frankel grade A in terms neurological recovery post decompression. It is a rare outcome that the motor power regained from 0 to 4, free from back pain and able to regain normal urinary and bowel function. As his surgery was a palliative surgery, his quality of life had improved markedly.